Pemanfaatan zeolit alam klinoptilolite sebagai katalisator dalam alkoholisis minyak jarak - Ratna Sri Harjanti (Jurnal Rekayasa Proses, 2008)
The use of solid catalyst in alcoholysis can increase the purity of ester because the separation process of solid catalyst is simpler than that of liquid catalyst. Prior to the ester formation, the ethanol was activated by the zeolite, forming alkoxide molecules. These molecules can attack the carbonyl functional group at the triglyceride in Jatropha oil and form ester. Jatropha oil, ethanol, and clinoptilolite zeolite powder were added into an autoclave equipped with manometer, thermometer, sampling valve, and heater. The autoclave was then powered up and rotated, and sampling was performed at time interval of 10 minutes. The reaction was performed at a temperature of 120°C and an autoclave rotation speed 110 rpm, with varied catalyst percentage and ethanol-oil equivalent ratio. The conversion was determined by analyzing the glycerol concentration of the lower layer with acetyl method. This study confirms that clinoptilolite type zeolite is effective catalyst for alcoholysis of jatropha oil. When the ethanol-oil ratio was 12.55 mgek/mgek, the catalyst percentage was 2.56% weight, the glyceride conversion reached 73%.